Cities, Systems and Structures: an ontological approach to urban studies - Almeida, Rodrigo Nicolau (2018)
Ontological issues lie at the heart of the epistemological, methodological and theoretical discussions over the workings and operations of cities – however, as Castells and Zukin point out, they find themselves mired in the midst of the praxis of urban studies, for reasons not entirely clear. In this work we attempt to trace a path through the ontology of urban studies, attempting to show the reasons for this apparent omission, as well as showing convergent trends from various disciplines towards a constructed ontology. Attempting to advance these discussions, and focusing on the case of heritage studies, we analyse a set of analytical classes that can inform the construction of such a “shared language”, debating them as a phenomenologically constructed set of plausible entities and intentions. In line with that, we argue the need for a transparent phenomenological epistemology, synthetized with strands of complex system analysis, as well as the methodological implications of such processes. We conclude by tracing some possibilities and implications of these kinds of analysis for urban studies in general.